2006
DOI: 10.1016/j.ympev.2006.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of basal subfamilies of ants using 28S rRNA (Hymenoptera: Formicidae)

Abstract: For many years, the ant subfamily Ponerinae was hypothesized to contain the basal (early branching) lineages of ants. Recently the Ponerinae were reclassiWed into six poneromorph subfamilies based on morphological analysis. We evaluate this new poneromorph classiWcation using 1240 base pairs of DNA sequence data obtained from 28S rRNA gene sequences of 68 terminal taxa. The molecular tree supported the monophyly of the ant family Formicidae, with 100% parsimony bootstrap (PB) support and posterior probabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
40
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 44 publications
7
40
1
4
Order By: Relevance
“…To provide directionality to this unrooted tree, we compared a range of alternative root positions by attaching the outgroups to different branches based on a priori hypotheses from the literature and evaluating these alternatives within a likelihood framework. Rooting 1 corresponds to Leptanillinae as the sister group to all other ants, the prior hypothesis suggested by previous molecular work (17,20,21). Rooting 2 implies the monophyly of (Amblyoponinae plus Leptanillinae plus Tatuidris), an alternative topology consistent with evidence of shared morphological (18,26) and behavioral features between Amblyoponinae and Leptanillinae, including adult consumption of larval hemolymph and the use of geochilomorph centipedes as prey (6,19,(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…To provide directionality to this unrooted tree, we compared a range of alternative root positions by attaching the outgroups to different branches based on a priori hypotheses from the literature and evaluating these alternatives within a likelihood framework. Rooting 1 corresponds to Leptanillinae as the sister group to all other ants, the prior hypothesis suggested by previous molecular work (17,20,21). Rooting 2 implies the monophyly of (Amblyoponinae plus Leptanillinae plus Tatuidris), an alternative topology consistent with evidence of shared morphological (18,26) and behavioral features between Amblyoponinae and Leptanillinae, including adult consumption of larval hemolymph and the use of geochilomorph centipedes as prey (6,19,(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 56%
“…This interpretation is contradicted by several molecular divergence dating studies that consistently estimate older ages for ants (14)(15)(16)(17). Molecular data have also generated some surprising phylogenetic results, including the conclusion that the subfamily Leptanillinae, a group of specialized subterranean predators (18,19), is the sister group to the rest of the ants (17,20,21). This conclusion contradicts all previous hypotheses about ant relationships.…”
mentioning
confidence: 88%
“…In addition, phylogenetic analyses have shown that different groups of genera formally within Ponerinae s.l. are more closely related to other subfamilies than among themselves (Keller, 2000;Ward and Brady, 2003;Saux et al, 2004;Brady et al, 2006;Moreau et al, 2006;Ouellette et al, 2006). Such accumulation of evidence led Bolton (2003) to propose the elevation of the major tribes within the old assembly to subfamily status, hence splitting the group into six subfamilies and restricting the name Ponerinae to the subgroup of genera mostly corresponding to the previously recognized tribe Ponerini.…”
Section: Introductionmentioning
confidence: 99%
“…KELLER: PHYLOGENETIC ANALYSIS OF ANT MORPHOLOGY Brady et al, 2006;Moreau et al, 2006;Ouellette et al, 2006), with analyses sampling several nuclear and mitochondrial gene regions for all recognized extant subfamilies or specific large portions of the ant phylogenetic tree. In contrast, comprehensive morphological data sets above the genus level have only been compiled for the dorylomorphs , Pseudomyrmecinae (Ward, 2001;Ward and Downie, 2005), and Myrmeciinae (Ward and Brady, 2003).…”
mentioning
confidence: 99%
“…These ants are distributed throughout the world's zoogeographic regions and occupy a great diversity of ecological niches, from both small and cryptic, to large and remarkable (Ouellette et al, 2006). The poneromorph ants have a great ecological importance, occupying different trophic levels (Brandão et al, 2011), thus participating in mutualistic plant associations (Pereira et al, 2013), facilitating seed dispersal (Leal et al, 2014).…”
mentioning
confidence: 99%